Translation, cultural adaptation, initial reliability, and validation of Turkish 15D's version: A generic health-related quality of life (HRQoL) instrument - İŞCİ, EMRE; GÖZÜ, HÜLYA (My University, 2005)
This article describes the adaptation of the Finnish 15D standardized measure of health-related quality of life (HRQoL) instrument for use in Turkey and assesses its psychometric properties. The HRQoL is measured in a sample of 75 patients with Type 2 diabetes using both 15D and Nottingham Health Profile (NHP) instruments. The internal consistency within the domains of 15D was high, with Cronbach's alpha values 0.89 for 15D scale and 0.89 for NHP. Significant correlations were observed between the scores of similar domains of 15D and the NHP in general health perception supporting the construct validity of the new 15D Turkish version. Overall, the results indicated that the adaptation of the 15D for use in Turkey was successful. The Turkish version was found to be a reliable and valid instrument. It is suitable and applicable to both clinical and population-based studies for the measurement of HRQoL in Turkey.
Keywords: Chronic disease; Health-related quality of life (HRQoL); Nottingham Health Profile (NHP); Turkish version of 15D; Type 2 diabetes; Validation